Pertanggungjawaban Notaris Akibat Ketidak hati-hatian - Moh. Saleh; Rinda Aveyuana Djami (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Notaries in carrying out their duties and responsibilities are required to always apply the precautionary principle, this is intended so that the notary can provide the best service for the community, besides that the notary who does not apply the precautionary principle may be subject to sanctions. The formulation of the research problem is: How is the precautionary principle applied in proving the formal validity of the identity documents of the appearers? What is the legal responsibility of a Notary in the event of falsification of documents in the form of the identities of the appearers? The research uses normative juridical law research with secondary data. The results show that the application of the precautionary principle can be carried out, starting with asking for the original document as a condition for making the deed, and notaries who do not apply the precautionary principle can be subject to sanctions both civil and criminal.Keywords: Prudential Principle; Accountability; Notary AbstrakNotaris dalam melaksanakan tugas dan tanggungjawabnya diwajibkan untuk selalu menerapkan prinsip kehati-hatian hal tersebut dimaksudkan agar notaris dapat memberikan pelayanan terbaik bagi masyarakat selain itu juga terhadap notaris yang tidak menerapkan prinsip kehati-hatian dapat dikenakan sanksi. Rumusan masalah penelitian ini yaitu: Bagaimana penerapan prinsip kehati-hatian dalam membuktikan keabsahan formil dokumen identitas para penghadap? Bagaimana tanggung jawab hukum Notaris bila terjadi pemalsuan dokumen berupa identitas para penghadap? Penelitian menggunakan Penelitian hukum yuridis normatif dengan Data sekunder. Hasil penelitian menunjukan bahwa Penerapan Prinsip Kehati-hatian dapat dilakukan, diawali dengan meminta warkah asli sebagai syarat dalam pembuatan akta serta terhadap notaris yang tidak menerapkan prinsip kehati-hatian dapat dikenakan sanksi baik itu secara perdata maupun pidana.Kata Kunci: Prinsip Kehati-Hatian; Pertanggungjawaban; Notaris.